Customers' relationship with their main grocery retail: an empirical study in the portuguese context - sandra filipe; Marques, S.; Salgueiro, M.F. (LBCR European Marketing Conference 2015, 2015)
Portugal has a large concentration of food retail distribution activity in a small number of large operators: Sonae Group, Gerónimo Martins Group, Dia Group, Auchan Group, Intermarché Group. In recent years, intense competition in the grocery retail market has increased the need for retailers to use strategies focused on attracting new customers and retaining current ones. Moreover, academic literature emphasises the concept of relationship marketing, and highlighting that the ultimate expected result from the formation of a successful relationship occurs through constructs such satisfaction, trust and loyalty. Specifically concerning current customers, it is important to examine their affiliation with the main grocery retailer, in which they make most of their purchases. Additionally, it is also important to examine the determinants of this relationship, by analyzing the consumer profile and the characteristics of the retailer. The socio-demographic profile of the respondents (including income level, education background, employment status and household size) and the psychographic profile (affinity with the convictions and motivations of the retailer) are known from the literature to have an influence on consumer's satisfaction, and in their decision to trust and stay loyal to the retailer. Also, the characteristics of the retailer, for example the store format and the existence of a loyalty card, are recognized in the literature to have an influence on the constructs of relationship marketing. Thus, the current research focuses on the study of the relationship between consumers and their main grocery retailer, aiming to better understand the factors that influence consumers' satisfaction, trust and loyalty with their main grocery retailer. In order to provide relevant theoretical and practical contributions to relationship marketing, this research addresses three main points: (1) to analyze the degree of satisfaction, trust and loyalty of the Portuguese consumers with their main grocery retailer (2) to characterize the socio-demographic and psychographic characteristics of the consumers that influence the relationship with their main grocery retailer; (3) to identify the characteristics of the grocery retailer that influence the relationship with their customers. Exploratory interviews with directors of stores with different formats were used. Collected data were subject to qualitative analysis. Additionally, a convenience sample of 992 Portuguese consumers answered to a questionnaire available online between 3 and 23 of February 2015. The collected data were analyzed using statistical techniques in SPSS 22.0 and AMOS 20.0.